An Investigation of the Concrete Contribution to Shear Strength of RC Columns Failing in Flexure - Arslan, Guray; Borekci, Muzaffer; Balci, Muzaffer; Hacisalihoglu, Melih (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
The contribution of concrete to an inelastic deformation capacity and shear strength of reinforced concrete (RC) columns failing in shear has been investigated extensively by various researchers. Although RC members are designed to have shear strengths much greater than their flexural strengths to ensure flexural failure according to the current codes, shear degradation of RC columns failing in flexure has not been studied widely. The aim of this study is to investigate the contribution of concrete to shear strength of RC columns using finite element analyses (FEA). The results of FEA are compared with the results of experimental studies selected from literature, and it is observed that the lateral load-deflection curves of analyzed columns are compatible with the experimental results. Twenty six RC columns were analyzed under monotonically increasing loads to determine the concrete contribution to the shear strength. The results of analyses indicate that increasing the ratio of shear to flexural strength reduces the concrete contribution to the shear strength of the columns.
Keywords: Reinforced concrete; Column; Concrete contribution; Shear strength; Flexural failure; Finite element; CAPACITY; MODEL; DEGRADATION; Engineering